The researcher's guide to solid-state dye-sensitized solar cells. Issue 44 (11th October 2018) - Benesperi, Iacopo; Michaels, Hannes; Freitag, Marina
Abstract : Solid-state dye-sensitized solar cell components, materials, architectures and interfaces are comprehensively reviewed. Abstract : In order to sustainably support its ever-increasing energy demand, the human society will have to harvest renewable energy wherever and whenever possible. When converting light to electricity, silicon solar cells are the technology of choice to harvest direct sunlight due to their high performance and continuously dropping price. For diffused light and indoor applications, however, silicon is not the material of choice. To power the next gizmo in your smart home, dye-sensitized solar cells (DSCs) are a viable alternative. Made from inexpensive, earth-abundant, and non-toxic materials, DSCs perform best at low light intensity. So far, issues such as leakage of the liquid electrolyte and its corrosive nature have limited the commercialization of this technology. To overcome these limitations, solid-state DSCs (ssDSCs) – in which the liquid electrolyte is replaced by a solid material – have been developed. For many years their efficiencies have been poor, preventing them from being widely employed. In the past six years, however, research efforts have led them to rival with their liquid counterparts. Here, we will review recent advancements in the field of ssDSCs. Every device component will be acknowledged, from metal oxides and new dyes to novel hole transporters, dopants, counter-electrodes and device architectures. After reviewing materials, long-term stability of devices will be addressed, finally giving an insight into the future that awaits this exciting technology.